(untitled) (Research, Society and Development, 2024)
Neoplasms have been growing considerably every year in Brazil and worldwide, and are the second leading cause of death. In addition, the rise in the incidence of mortality reinforces the need to implement strategies for prevention, early detection, treatment and palliative care, especially in Primary Health Care, which is the user’s main gateway to the Unified Health System. In this scenario, nurses are an important figure in implementing these strategies for the prevention and early detection of neoplasms. Objectives: identify the ways in which nurses can act in the early detection of cancer, as well as describe the tools used and the obstacles that make your work difficult. Methodology: this is a integrative review of the literature carried out from january to july 2024. The descriptors used were: “oncology nursing”, “early detection of cancer” and “oncology”, taken from the Health Sciences Descriptors. Results: 349 articles were found, combined with each other by the Boolean operator “AND” during the period from january 2013 to july 2024. It consisted of a final sample of 11 articles related to the variable of interest. Final considerations: It was possible to observe that actions aimed at early detection of cancer are extremely important for diagnosis and treatment, requiring continued education for the development of early diagnosis, in addition to carrying out measures aimed at preventing different types of cancer.